Bioethanol Production From Green Algae Spirogyra sp - Danang Jaya; Rahayu Setiyaningtyas; Sudiyono Prasetyo (Eksergi, 2018)
Bioethanol is an alternative fuel that has potential to replace the oil fuel. The bioethanol feedstock can be derived from the green algae Spirogyra sp that is rarely exploited. High carbohydrates content in the Spirogyra sp algae is highly potential to be developed into ethanol through chemical and biological processes. This research is done through several stages: preparation of raw material, hydrolysis using sulfuric acid 0,2 M, and fermentation using Saccharomyses cerevisiae in an anaerob condition. The objective of this study is to find out the optimum reaction time and optimum quantity of Saccharomyses cerevisiae in the fermentation process. Variations of reaction time and yeast quantity are applied; those are 3, 4, 5 and 6 days for reaction time, and 0,5%; 0,75%; 1%; 1,25%; 1,5%; and 1,75% for yeast quantity. The stoichiometric calculation is used to analyse the result of this experiment. The result shows that the optimum duration for the fermentation is 5 days and the optimum quantity of yeast is 1% by weight. The condition of fermentation process must be held in pH of 4,5 and temperature of 30oC. The produced alcohol in those condition is 0,0613 mol.